Application of a simple headcut advance model for gullies. Issue 1 (22nd September 2017) - Allen, Peter M.; Arnold, Jeffrey G.; Auguste, Lance; White, Joseph; Dunbar, John
Abstract: Gully erosion begins in streambanks and uplands as a consequence of adjustments in driving forces on the landscape imposed by changes in land use or climate. The deleterious effects of gullies worldwide have led to many site‐specific studies of gully form and function. In the continental United States, gully erosion in agricultural land has destroyed valuable farmland yet, prediction of gully processes remains problematic on a national scale. This research has proposed a simple method to predict gully headcut advance. When combined with SWAT hydrologic flow routines, the model predicted gully headcut advance with reasonable accuracy on a daily time step for time periods exceeding two decades. The model was tested in two distinct land resource areas of the United States with differing climate, soils, cover and drainage. The inputs for the headcut model have been kept simple as the model will be applied over large areas. Model inputs consist of headcut height, headcut resistance (based on soil erodibility and a root‐cover factor), and daily flow. The model is compared with an annual time step model used in assessment of headcut advance and appears to offer a better way to assess gully headcut advance. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A simple headcut migration model is proposed as a first step in assessing the time rate of advance in gullied watersheds in the United States. The model is driven by a continuous daily timestep water balance model. Headcut advance and basal scour is dependent on headcut height and discharge which is in turn modulated by a soil/vegetation/root parameter. Results appear to be reasonable for clay to loam textured soils.